Performance degradation of polymer material under freeze-thaw cycles: A case study of extruded polystyrene board - Niu, Fujun; Jiang, Haiqiang; Su, Wenji; Jiang, Wangtao; He, Junlin (Polymer testing, 2021)
Polymer materials, such as extruded polystyrene (XPS), polyurethane (PU) and polystyrene (EPS), are extensively used as thermal insulators in cold regions to protect the engineering from frost damage. However, the performance degradation caused by freeze-thaw cycles (FTC) of polymer material has not been fully quantified. To fill this gap, a series of experiments were carried out by taking XPS board as the test material. After the XPS board was subjected to hundreds of FTC, the volumetric water absorption, thermal conductivity, uniaxial compressive strength and Young's modulus as well as creep strain were measured and analyzed. The results demonstrate that the volumetric water absorption and thermal conductivity change slightly with the FTC. After 400 times of FTC, the volumetric water absorption increased within only 0.1% and the thermal conductivity decreased within 9 × 10−4 W⋅(m⋅K)−1. Additionally, the uniaxial compressive strength and Young's modulus decrease with the increasing of FTC, and the effect of FTC on Young's modulus is mainly concentrated in the first 50 times. The creep behavior of XPS board belongs to decay creep and the exponential function can describe the creep process well. The results obtained in this study may help us to understand the degradation of XPS board and provide references for the design of controlling engineering damages caused by FTC in cold regions. •The performance degradation of XPS board under freeze-thaw cycles is quantified.•The creep equation of XPS board is established.•The relationships between volumetric water absorption, thermal conductivity and density of XPS board are determined.